2020
DOI: 10.1590/1984-0462/2020/38/2018319
|View full text |Cite
|
Sign up to set email alerts
|

Bathing, Make-Up, and Sunscreen: Which Products Do Children Use?

Abstract: Objective: To evaluate the hygiene practices and frequency of use of personal hygiene products, cosmetics, and sunscreen among children and adolescents. Methods: Cross-sectional study with interviews about skincare conducted with caregivers through closed-ended questions. We included patients up to 14 years of age waiting for consultation in pediatric outpatient clinics of a tertiary hospital. We performed a descriptive statistical analysis and applied the Kruskal-Wallis test and Fisher’s exact test to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The most appropriate time to introduce photoprotection habit is during childhood, which is the period of greatest sun exposure 14,16 . Like many studies, although most (93.5%) of our study participants reported knowing the harmful effects of sunlight, regular use of sunscreen was low (27.4%) 7,14,16,17 …”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The most appropriate time to introduce photoprotection habit is during childhood, which is the period of greatest sun exposure 14,16 . Like many studies, although most (93.5%) of our study participants reported knowing the harmful effects of sunlight, regular use of sunscreen was low (27.4%) 7,14,16,17 …”
Section: Discussionmentioning
confidence: 61%
“…This can lead to irritant contact dermatitis and exacerbate underlying skin conditions, such as acne and rosacea. 1,[3][4][5][6][7][8] Our results showed that most adolescents had correct knowledge about skin cleansing, but some did not know the appropriate pH of the cleanser (37.8%) and the correct bathing duration (55.8%). Dissimilar…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…37 However, the use of makeup and harsh skincare products, particularly among adolescents, could act as external damaging agents. 38 Sunscreen use is important in preventing or delaying photoageing by protecting the skin against UVR damage. However, real-world sunscreen use often falls short of what is recommended, and consumer compliance depends largely on preferences for product aesthetics and concurrent use with other facial products.…”
Section: Recommendations For Detecting and Delaying Preageingmentioning
confidence: 99%